1996
DOI: 10.1002/art.1780390419
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous hereditary C1q deficiency and systemic lupus erythematosus: A new family and the molecular basis of C1q deficiency in three families

Abstract: Objective. To describe a new kindred with Clq deficiency and to identify the molecular lesions responsible for complete functional Clq deficiency in this and 2 other previously described kindreds.Methods. The A-, B-, and C-chain genes of Clq were amplified by polymerase chain reaction, cloned, and sequenced. The DNA sequence was checked for mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(30 citation statements)
references
References 8 publications
0
28
0
1
Order By: Relevance
“…The last question is whether this in vitro phenomenon has any relevance to in vivo situations. Phagocytosis was suggested to be defective in lupus patients due to rare genetic defects such as complement deficiencies (48) or specific alleles such as Fc␥RIIIa (49). Studies of handling of immune complexes showed that both FcR and complement receptors are saturable (50 -53).…”
Section: Discussionmentioning
confidence: 99%
“…The last question is whether this in vitro phenomenon has any relevance to in vivo situations. Phagocytosis was suggested to be defective in lupus patients due to rare genetic defects such as complement deficiencies (48) or specific alleles such as Fc␥RIIIa (49). Studies of handling of immune complexes showed that both FcR and complement receptors are saturable (50 -53).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular basis of C1q deficiency is single base-pair mutations leading to termination codons, frame shift, or amino acid exchange in each one of the three C1q genes (a, b, and c) associated with absence of detectable protein or expression of reduced levels of dysfunctional protein (5,6,11,12). Although these homozygous C1q deficiencies are a strong risk factor in SLE, they are rare in lupus patients overall (7,13,14).…”
Section: S Ystemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
“…Complete deficiency of the early components C1q, C2 and C4 of the classical pathway of complement are associated with a most striking risk to developing SLE [31][32][33][34][35][36][37][38][39][40][41][42][43]. Deficiency of C4A, so called C4Anull, is probably the most commonly inherited complement deficiency, occurring in varying frequency in different populations [44].…”
Section: Studies Of Candidate Genesmentioning
confidence: 99%